Investigation on performance of battery thermal management system using spray cooling. (16th February 2022) - Fan, Zhuoxuan; Wang, Yanan; Xie, Zongfa; Wang, Zhengkun
Summary: The thermal management system has essential effects on the performance, life, and consistency of lithium‐ion batteries. Compared with commonly used cooling methods, spray cooling has excellent performance and is now widely used in electronic equipment, metal processing, laser surgery, and other fields. However, there are few applications of spray cooling in the battery thermal management systems (BTMSs). With the increase of the charge and discharge speed and people's rising attention to the thermal runaway accidents of electric vehicles, it is urgent to intensively investigate the performance of spray cooling in the BTMS and discuss its design method. In this research, a BTMS using spray cooling was designed with pouch‐type lithium‐ion cells and injectors. A synthetic lubricant was used as the spray medium. The electrical–thermal coupled model was adopted to obtain the heat production and temperature distribution of the cell. Numerical calculation and analysis of the spray cooling process were performed based on the discrete phase model. It was found that spray cooling could reduce the maximum temperature (MAT) on the cell from 53.6°C to 39.7°C during the 3 C discharge process and the maximum temperature difference (MATD) from 9.1°C to 6.0°C. And the temperatures of the tabs were also reduced. The effects of the spray speed, the mass flow rate, the specific heat capacity, and the droplet size on the performance of the BTMS using spray cooling were further investigated. The results showed that within a certain range, increasing the mass flow rate and specific heat of the spray, or decreasing the average diameter of the droplets could reduce both the MAT and the MATD on the cell. But their effects on the latter were not significant. When the spray speed was increased, the MATD demonstrated a monotonous decreasing trend and could be reduced to below 5°C. Abstract : Temperature distributions on the cell with natural convection cooling, forced air cooling and spray cooling